Why are We Here? The Educational Value Model (EVM) as a Framework to Investigate the Role of Students' Professional Identity Development - Nylen, Aletta; Daniels, Mats; Pears, Arnold; Cajander, Asa; McDermott, Roger; Isomottonen, Ville (Proceedings - Frontiers in Education Conference, 2018)
Education can be seen as a preparation for a future profession, where some educational programs very clearly prepare their students for a certain profession, e.g. plumber, nurse and architect. The possible professions for students following education programs in computing is quite varied and thus difficult to cater for, but to educate towards a professional life is still a stated goal in most higher education settings. We argue that this goal is typically not even closely reached and provide an analysis indicating factors explaining this situation. The analysis is based on the concept of professional identity.In earlier work [1] a framework with which to reason about student interactions with the regulatory structure of higher education and teachers was developed. In that paper we developed a compound model which not only relates these players to one another, but also provides approaches to reasoning about misalignments which arise when students and teachers approach their shared learning context from different perspectives. This framework is in this paper applied to address different aspects of professional identity with the intent of bringing forth deeper insights into challenges with educating towards professions. This issue is highly complex and the framework provides a structure that is beneficial for analysing different aspects in a more holistic manner.